Exploring the issues of Primary School students’ mastery of Jawi and the ICT solution - Abdul Malik, Marliza; Osman, Salyani; Marjudi, Suziyanti; Ahmad Nawi, Haslinda Sutan; Mohd Noor, Suhaimi; Bamasoud, Doaa M (Journal of ICT in Education, 2024)
Jawi writing serves as the principal medium for Islamic education instruction in schools today. Possessing proficient Jawi writing skills enables students to effortlessly navigate the learning process and gain a comprehensive understanding of Islamic education content. This study aims to investigate the current state of mastering Jawi writing skills among primary school students in one of the most developed and progressive states in Malaysia. A comprehensive literature review and surveys of 33 parents were done. Apart from this, an interview was conducted with teachers from three different types of religious primary schools: Religious Primary Schools (Sekolah Rendah Agama), Integrated Religious Primary Schools (Sekolah Rendah Agama Integrasi), and Al-Quran and Fardu Ain Integration Classes. The literature review, survey, and interview results clearly demonstrate that students face significant difficulties when learning to connect Jawi letters into words. The survey and interview responses highlighted the importance of providing adequate practice and reinforcement opportunities for students. Considering these findings, it is crucial to develop new teaching strategies and materials such as integration of Information and Communication Technology (ICT) tools such as educational software, interactive digital whiteboards, and customized learning apps specifically designed to support the learning and mastery of Jawi writing. These ICT solutions could provide engaging, interactive, and differentiated learning experiences tailored to student needs, thereby potentially improving proficiency in Jawi writing among primary students.